Impact of three intense winter cyclones on the sea ice cover in the Barents Sea: A case study with a coupled regional climate model - Aue, Lars; Röntgen, Leonie; Dorn, Wolfgang; Uotila, Petteri; Vihma, Timo; Spreen, Gunnar; Rinke, Annette (Frontiers in Earth Science, 2023)
We utilize a nudged simulation with the coupled regional atmosphere-ocean-sea ice model HIRHAM-NAOSIM over the Arctic to conduct an in-depth analysis of the impact of a sequence of three intense cyclones on the sea ice cover in the Barents and Kara Seas in February 2020. To clarify the underlying mechanisms we decompose changes in sea ice concentration (SIC) and thickness (SIT) into their dynamic and thermodynamic contributions and analyze them in concert with simulated changes in the wind forcing and the surface energy budget. Our findings reveal that changes in SIT during and after the cyclone passages are mostly driven by dynamic processes such as increased ice drift and deformation. With respect to SIC, the relative importance of dynamics and thermodynamics depends on the considered time scale and on the general conditions of the cyclone passages. If cyclones follow on each other in rapid succession, dynamic mechanisms dominate the SIC response for time scales of more than two weeks and thermodynamic effects via advection of warm-moist/cold-dry air masses on the cyclone's front/back side only play a secondary role. However, if sufficiently long time elapses until the arrival of the next storm, thermodynamic SIC increase due to refreezing under the influence of cold and dry air at the backside of the cyclone becomes the dominating mechanism during the days following the cyclone passage.